1982
DOI: 10.1007/bf00283745
|View full text |Cite
|
Sign up to set email alerts
|

Reflex control of heart rate in normal subjects in relation to age: A data base for cardiac vagal neuropathy

Abstract: We examined the heart rate changes induced by forced breathing and by standing up in 133 healthy subjects in the age range 10-65 years in order to establish a data base for studies on parasympathetic heart rate control in autonomic neuropathy. Test results declined with age. Log-transformation was used to define the lower limit of normal (P0.10) and an uncertainty range (values between P0.10 and P0.025). The lower limit of normal decreased from 22 to 11 beats/min for forced breathing and from 26 to 16 beats/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
100
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(120 citation statements)
references
References 16 publications
(18 reference statements)
18
100
2
Order By: Relevance
“…Especially in an elderly population this could be problematic, as is also shown by the higher number of missing values for this test. Poor agreement between heart-rate changes during deep breathing and after standing up has also been reported in a study of 133 healthy subjects in the age range of 10 to 65 years, where they found a correlation between EI difference and RR max of 0.17 and between EI difference and RR max/min of 0.14 [17]. An explanation might be the possible involvement of different afferent and efferent mechanisms [49].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Especially in an elderly population this could be problematic, as is also shown by the higher number of missing values for this test. Poor agreement between heart-rate changes during deep breathing and after standing up has also been reported in a study of 133 healthy subjects in the age range of 10 to 65 years, where they found a correlation between EI difference and RR max of 0.17 and between EI difference and RR max/min of 0.14 [17]. An explanation might be the possible involvement of different afferent and efferent mechanisms [49].…”
Section: Discussionmentioning
confidence: 85%
“…For the computation of the BRS only spectral components were used that were within a defined band width (0.05-0.15 Hz) around the breathing frequency of six breaths per minute and with a squared coherence (γ 2 ) of 0.5 or higher. During an active change in position from lying to standing, the maximal change in RR interval (RRmax), defined as the difference between the mean RR interval during 1 min prior to standing up and the minimum RR interval within 15 s after standing up, was obtained [17]. Furthermore, we measured the maximum RR interval between 15 and 30 s after standing up divided by the minimum RR interval within 15 s after standing up (RRmax/min) [45] and the systolic blood pressure difference (SBP difference) after standing up calculated as the mean over 30 s during 1.5 to 2 min after standing up, minus the mean over 30 s prior to standing up [3].…”
Section: Study Population: Reference Values and Agreement The Hoornmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic function was investigated performing a battery of standard cardiovascular (CV) tests, previously described and currently used for the diagnosis of diabetic autonomic neuropathy [15][16][17][18]: (i) heart rate variation during deep breathing (DB) at 6 cycles/min; (ii) heart rate variation with postural change: (a) lying to standing test (LS) and (b) the increase in heart rate during the first 15 s after standing (SHR); (iii) heart rate variation to a standard Valsalva manoeuvre; (iv) postural blood pressure (PBP) test. Each test was performed by means of a computerized method (Autocheck 'r' 3, vers.…”
Section: Assessment Of Autonomic Functionmentioning
confidence: 99%
“…5.1 software; K. Thomaseth and F. Bellavere, Padua, Italy); blood pressure was recorded using a Finapres device (Ohmeda, Denver, CO) for beat to beat blood pressure monitoring. The tests were graded as normal, borderline or abnormal with a score of 0, 1 or 2, respectively, using age-related normal ranges previously published [16,18]. Autonomic dysfunction was defined with a total score Ն 5 [19].…”
Section: Assessment Of Autonomic Functionmentioning
confidence: 99%